2020
DOI: 10.1111/desc.13031
|View full text |Cite
|
Sign up to set email alerts
|

The role of the corpus callosum in language network connectivity in children

Abstract: The specific role of the corpus callosum (CC) in language network organization remains unclear, two contrasting models have been proposed: inhibition of homotopic areas allowing for independent functioning of the hemispheres versus integration of information from both hemispheres. This study aimed to add to this discussion with the first investigation of language network connectivity in combination with CC volume measures. In 38 healthy children aged 6–12, we performed task‐based functional magnetic resonance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 81 publications
(105 reference statements)
2
15
0
Order By: Relevance
“…The findings in ACC patients are in line with previous research in healthy children and adolescents, showing that bilateral language representation is favourable for language abilities ( Bartha-Doering et al 2018a ). The present study furthermore resumes a recent study from our lab that demonstrated the integrative function of the posterior CC in functional language network connectivity, fostering improved interhemispheric functional connectivity and enhanced language abilities in healthy children ( Bartha-Doering et al 2020 ). Interestingly, some previous studies point to different effects of the CC on language lateralization in temporal and frontal brain areas dependent on the nature of task.…”
Section: Interhemispheric Connectivity In Accsupporting
confidence: 84%
See 2 more Smart Citations
“…The findings in ACC patients are in line with previous research in healthy children and adolescents, showing that bilateral language representation is favourable for language abilities ( Bartha-Doering et al 2018a ). The present study furthermore resumes a recent study from our lab that demonstrated the integrative function of the posterior CC in functional language network connectivity, fostering improved interhemispheric functional connectivity and enhanced language abilities in healthy children ( Bartha-Doering et al 2020 ). Interestingly, some previous studies point to different effects of the CC on language lateralization in temporal and frontal brain areas dependent on the nature of task.…”
Section: Interhemispheric Connectivity In Accsupporting
confidence: 84%
“…Although language is predominantly processed in the left hemisphere in most healthy children ( Szaflarski et al 2002 , 2012 ), stronger functional connectivity with the right hemisphere enables better verbal abilities ( Bartha-Doering et al 2020 ). Thus, the CC seems to play an excitatory role in the integration of information of both hemispheres and language abilities profit from additional right hemisphere language processing that support and interact with left hemisphere processing.…”
Section: Hemispheric Specializationmentioning
confidence: 99%
See 1 more Smart Citation
“…Two contrasting models have been suggested. According to the excitatory model, the callosal fibers integrate information from both cerebral hemispheres to facilitate interhemispheric connectivity ( Bartha‐Doering et al, 2021 , Gazzaniga, 2000 ). By contrast, the inhibitory model postulates that callosal fibers inhibit homologous areas, which allows for independent functioning of the hemispheres ( Cook, 1984 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is has been shown that the variation in the microstructure of the CC can strongly affect visuospatial perception and verbal fluency tasks, as well as other cognitive functions such as memory which may result in serious cognitive disorders [53][54][55]. The positive correlation of the posterior callosum with verbal fluency and language lateralization and also the anterior callosum with visuospatial ability has been demonstrated [56][57][58].…”
Section: Discussionmentioning
confidence: 99%